Comparative Analysis of High Speed Carry Skip Adders - Naga Babu, Ch; Naga Siva Sai, P; Priyanka, Ch; Hari Kishore, K; Bindu Bhargavi, M; Karthik, K (International Journal of Engineering and Technology, 2018)
In this paper we compared a high speed carry skip adders by considering parameters such as area, LUTâ€™S, delay, power. When compared to conventional CSKA and other adders. Here in this project in first stage CSKA designed by using multiplexer as skip logic so by using this speed gets increased by skipping of carry. so here area gets increased so to reduce area another hybrid variable latency carry skip adder(Brent-kung adder) is designed .here power utilization also gets decreased, speed gets increased, but some delay is produced here to overcome that we followedÂ a another method called Kogge-Stone adder here so it reduces the critical path delay. In Kogge-stone adder power is highly consumed due to more no of wiring connections so another adder was designed to reduce power consumption which is Sklansky adder which reduces power Consumption. This is done in Xilinx ISE 14.7 and power was analyzed using Xilinx power analyzer. Â